A comprehensive analysis of the (√13 × √13)R13.9° type II structure of silicene on Ag(1 1 1). (20th April 2016) - Jamgotchian, H; Ealet, B; Maradj, H; Hoarau, J-Y; Bibérian, J-P; Aufray, B
Abstract: In this paper, using the same geometrical approach as for the (2 √ 3 × 2 √ 3) R 30° structure (Jamgotchian et al 2015 J. Phys.: Condens. Matter 27 395002), for the (√13 × √13) R 13.9° type II structure, we propose an atomic model of the silicene layer based on a periodic relaxation of the strain epitaxy. This relaxation creates periodic arrangements of perfect areas of (√13 × √13) R 13.9° type II structure surrounded by defect areas. A detailed analysis of the main published experimental results, obtained by scanning tunneling microscopy and by low energy electron diffraction, shows a good agreement with the geometrical model.